Effects of melon (Citrullus lanatus Thunb.) and okra (Abelmoschus esculentus [L.] Moench) on the soil moisture and leaf water status of intercropped cassava/maize in Nigeria - Ikeorgu, J.; Wahua, T.; Ezumah, H. (1989)
A two year trial was conducted a11badan to determine the effects of okra and melon on the soil moisture and leaf water status of cassava/maize intercrops. Inclusion of melon into a cassava/maize mixture. Especially where the cassava had sparse canopy, appeared to be an effective means of conserving soil moisture, increasing leaf water status and yield. From the diffusive resistance values of cassava in a cassava/maize! melon mix were at seven weeks after planting (WAP), there were, however, strong indications that melon might be competitive during periods of prolonged drought or low rainfall, where and when reduction in soil temperature. Soil moisture stress and a complete soil cover to cheek erosion are of great importance. Melon could be better intercrop than okra.